Association of Metabolic Syndrome with Body Fat Percent, Anthropometric Indices in 10 To 18 Year Old Adolescents. - Parvin Mirmiran; Mansoureh Rezaei; Golaleh Asghari; Yadollah Mehrabi; Fereidoun Azizi (Tehran University of Medical Sciences, 2014)
Our aim was to evaluate the association of metabolic syndrome (MetS) and its components with body fat percentage (BFP) and anthropometric indicesin10 to 18year old adolescents.This was a cross-sectional study conducted on 134 Tehranian adolescents, aged 10 to 18 years (66 boys and 68 girls) in 2007. The MetS definition proposed by Cook et al. was used. Logistic regression was used to determine the relationship of MetS and its components with body mass index (BMI), waist circumference (WC), waist to height ratio (WHtR), and BFP. Using the areas under the receiver operating characteristic (ROC) curve, the discriminatory ability of anthropometric measurements and BFP was evaluated.The mean±SD forage of boys and girls was14.5±2.3and13.0±2.9 years, respectively (P=0.001); the prevalence of MetS in these groups was 32.3 and6.5%, respectively (P=0.001). After adjusting for sex and physical activity, the highest odds ratios (95% CI) for MetS and hypertriglyceridemia were found for WC, 6.27 (2.63-14.94; P